PERCEPTION OF SEVERITY LEVEL AND DECISION MAKING OF FAMILY CORRELATION TOWARD DEPARTING INTERVAL OF ISCHEMIC STROKE PATIENT - Rahmawan, Fajri Andi; Yueniwati, Yuyun; Suharsono, Tony (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2020)
Background: Ischemic stroke is an emergency state condition of brain which needs immediate rescue so the sufferer will not get any injury or risk of death. Interval of departing period still becomes problem. Level of severity perception and process of decision making of family are factors correlated to interval of departing time of the patient to Emergency Department.Objective: The purpose of this research is to find out correlation of severity level perception and process of decision making of family to interval of departing time of patient suffering stroke to Emergency Department of Public Regional Hospital Blambangan Banyuwangi.Methods: The method of this research is quantitative with cross sectional approach by involving 113 respondents. The technique of sampling is purposive sampling. The instruments are interview and observation sheet. The data analysis is done by spearman test to find out the correlation between variables namely level of severity and process of decision making of family’s patient to interval of departing time.Results: Findings show that p value between perceptions of severity level to the interval is 0.000 and process of decision making of the family to the interval with p value = 0.000 < α 0.05 meaning that variable of severity level and process of decision making are correlated to interval of departing time.Conclusion: Nurses need to improve standard of stroke severity by determining half-body weakening symptom into severity of ischemic stroke then it is socialized to society and to let them know the importance of immediate transport to emergency department when ischemic stroke symptom is found